Cash Management and Financial Performance of Business Firms in Northern Uganda a Case of Lira District - Eton, Marus; Gilbert, Uwonda; Fabian, Mwosi; Benard, Patrick Ogwel; Dennis, Obote (The International Journal of Business Management and Technology, 2019)
The study sought to establish the effect of cash management on financial performance of business entities in Lira district. A cross sectional study design was adopted and data was collected by use of structured and closed ended questionnaire. Business owners who took part in the study confirmed high abilities in managing cash receivable, holding inventories and properly generating sufficient cash for meeting immediate obligations. However, the study found that the aforementioned practices were not sustainable with time due to incompetence in forecasting receipts and payments. This led to a conclusion that cash management has an insignificant effect on financial performance. The study recommended that Business associations like Uganda Chamber of Commerce, Uganda Manufacturers Association, in addition to Ministry of Trade and Commerce should consider providing trainings on cash management to existing and upcoming entrepreneurs to support them in developing cash management and other necessary business skills. There is also need for business owners to consider hiring business experts who can use different statistical models to forecast business performance.